Organizational Communication : Abstracts, Analysis, and Overview (Volume.9) - Greenbaum, Howard H. [et al.] (Beverley Hills, London Sage Publications, 1984)
Volume 9 incorporates over 1,200 abstracts from material on organizational communication published during 1982-3. Like earlier volumes, this one begins with an invited review essay, the value of which is widely acknowledged. The current subject is communication feedback within organizations. Overall, Volume 9 continues to provide scholars, students and practitioners with the most reliable, up-to-date, and comprehensive guide to literature in the field of organizational communication. The series is jointly sponsored by the International Communication Association and the American Business Communication Association.
Include Appendices and Index.
Keywords: Communication in Organizations -- Communication in Management -- Bibliography